INVESTIGATING THE USE OF STORYTELLING TECHNIQUE TO ENHANCE SPEAKING SKILLS IN JUNIOR HIGH SCHOOL - Pratama, Dito Adi; Pujiawati, Nia; Utami, Praditya Putri (PROJECT (Professional Journal of English Education), 2024)
This study investigates a storytelling technique that can enhance the English language experience of eighth grade students. Using a qualitative case study design, the research explored students' motivation, confidence and overall speaking experience. Six students participated in semi-structured interviews and classroom observations. Thematic analysis revealed a narrative of transformation. Initially, the students showed enthusiasm and actively participated in discussions about storytelling techniques and narrative text structure (pre-storytelling). This enthusiasm became the basis for deeper engagement. Next, the students embark on a journey of deconstructing the story (storytelling guide). The study the building blocks of the story, exploring narrative elements and linguistic features. Finally, the students reach the pinnacle of their learning by presenting the chosen story, demonstrating a new understanding of narrative structure and expressing a surge of confidence (after storytelling). Further interviews reinforced this narrative. The students reported a significant increase in motivation and confidence when speaking English, with initial nervousness dissipating after repeated practice. Although initial challenges such as pronunciation anxiety were identified, the students expressed confidence that these would diminish with continued practice. The storytelling technique emerged as a powerful tool, fostering a positive and engaging learning environment that empowered students as active participants, instilled confidence in their speaking abilities.